β-Thromboglobulin and Deep Vein Thrombosis - Smith, R C; Duncanson, Jeanette; Ruckley, C V; Webber, R G; Allan, N C; Dawes, Joan; Bolton, A E; Hunter, W M; Pepper, D S; Cash, J D (Thrombosis and Haemostasis, 1978)
The measurement of plasma β-thromboglobulin as a potential diagnostic test for venous thrombosis has been investigated in 16 normal volunteers, 24 patients presenting with deep vein thrombosis (DVT) or pulmonary embolism and 46 patients screened by 125 I fibrinogen test (IFT) for post-operative DVT. The normal mean was 33 ng/ml (range 15-117 ng/ml). Of the 24 patients with clinical thrombotic disease 22 presented with DVT confirmed by phlebogram or IFT and 2 presented with embolism confirmed by lung scan. At the time of first presentation 12 out of 24 had βTG values greater than 70 ng/ml. All except 3 of this group of 24 patients had values of greater than 70 ng/ml at some stage during a subsequent week of daily sampling. DVT was detected in 13 out of 46 screened post-operative patients. There was a rise in βTG observed within 24 hr of the IFT becoming positive but the mean rise did not reach significance at the 5% level.An association between DVT and high βTG values has been confirmed. However, its clinical value cannot yet be fully elucidated until factors, probably related to blood sampling and clearance, are further investigated.